Becoming an architect : - Waldrep, Lee W. (John Wiley & Sons, Inc., 2006)
Becoming an Architect completely up-to-date guide to today's careers in architecture provides a clear and concise survey of the field and offers advice for navigating a successful career. Filled with interviews and insights from leading architects, the book covers everything from educational requirements and design specialties to registration requirements and the many directions in which a career in architecture can go.